2013
DOI: 10.1103/physreva.88.032901
|View full text |Cite
|
Sign up to set email alerts
|

Energy loss of low-energy ions in transmission and backscattering experiments

Abstract: The determination of the electronic stopping power for low-energy ions is an experimentally demanding task. In this paper we elaborate on the different effects of nuclear stopping and multiple scattering on the energy spectra for different experimental geometries, i.e., transmission through thin foils and backscattering from thin films. By calculating distributions of path lengths and scattering angles we demonstrate how electronic stopping, nuclear stopping, and multiple scattering add up to the total energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 43 publications
1
20
0
1
Order By: Relevance
“…by antiprotons [31][32][33] and by protons [34][35][36][37][38]) beards the theoretical developments. The expected linear dependence with the velocity, the influence of d-electron excitation and the density of electrons involved in the projectile loss of energy, have attracted many of the stopping power experimental efforts in the last years [39][40][41][42][43][44][45]. The theoretical work on low energy stopping is extensive, such as by the groups of Echenique [46,47], Nagy [48][49][50], Arista [17,[51][52][53], Cabrera-Trujillo [54], and more recently Kadyrov [18,55] and Grande [56].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…by antiprotons [31][32][33] and by protons [34][35][36][37][38]) beards the theoretical developments. The expected linear dependence with the velocity, the influence of d-electron excitation and the density of electrons involved in the projectile loss of energy, have attracted many of the stopping power experimental efforts in the last years [39][40][41][42][43][44][45]. The theoretical work on low energy stopping is extensive, such as by the groups of Echenique [46,47], Nagy [48][49][50], Arista [17,[51][52][53], Cabrera-Trujillo [54], and more recently Kadyrov [18,55] and Grande [56].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we skip here groups 7 to 12, where d-electrons play a quasi FEG role depending on the impact velocity. There are very interesting targets that have been an object of extensive experimental research in the last decade, focused on targets such as Pd, Pt, Cu, Ag, Cu, Au, or Zn [39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…However for He + (2 keV)/Ag(200 Å) and He + (10 keV)/Ag(800 Å) a strong contribution of transmitted ions with longer path lengths is observed. In such cases, we should use adequate methods such as the Monte Carlo simulations to describe trajectories of ions [3].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent publication [3] Monte Carlo simulations have been performed to study the determination of energy loss from transmission and backscattering experiments. It has been shown that the contribution of nuclear losses and multiple scattering becomes important for very low ion energy and/or for larger values of the target thickness.…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, since SRIM model parameters are fitted to experiments, predictions are sensitive to experimental errors, for example, in separating electronic and nuclear stopping contributions. 17 Hence, values obtained from SRIM carry numerous uncertainties, especially for heavy ions in the low-velocity range. 5 In collision cascades, projectiles travel in random directions, and recoils initiated in the bulk, for example, by neutron impacts or as secondary recoils in cascades, seldom the channel.…”
Section: Introductionmentioning
confidence: 99%